Virtual Ethnography in Anonymous Alcoholics in Times of Pandemic: Theoretical and Methodological Challenges - Edemilson Antunes de Campos (2021)
The purpose of this article is to understand how A.A. members carry out the treatment of alcoholism in the midst of the pandemic, through a virtual ethnography in A.A. groups in Brazil. A virtual ethnography was carried out in online recovery meetings of A.A. groups, located in the City of São Paulo-Brazil and interviews, via Google Forms, with A.A members from several Brazilian cities. With the pandemic, ethnography migrated to the virtual space, which has caused certain tensions in relation to the classic notion of fieldwork in anthropology, to the use of data collection techniques, such as participant observation and interview modalities. Thus, it seeks to contribute to the understanding of the way in which A.A. members carry out the treatment of alcoholism in online recovery meetings and, in this way, the theoretical and methodological challenges of virtual ethnography in times of pandemic.